The Effect of Lighting Program and Melatonin on the Alleviation of the Negative Impact of Heat Stress on the Immune Response in Broiler Chickens - Abbas, Ahmed O.; Gehad, Ahmed E.; Hendricks, Gilbert L.; Gharib, H.B.A.; Mashaly, Magdi M. (International Journal of Poultry Science, 2007)
Two experiments were conducted to study the effect of lighting program and melatonin addition to the diet on the immune responses of broiler chickens under chronic heat stress. In the first experiment, two groups of male broiler chickens received Continuous Light (CL) (23L: 1D) while another two groups received Intermittent Light (IL) (1L: 3D). From 4 to 6 wk of age, a group from each light program was exposed to 35 °C versus 24 °C for the other two groups. Heat stressed chickens under IL had significantly lower (p